2016
DOI: 10.1124/dmd.116.074211
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Zolpidem into Hair and Its Distribution after a Single Administration

Abstract: To obtain fundamental information on the drug incorporation into hair, time-course changes in drug distribution along single-strand hair were observed after a single oral administration of zolpidem (ZP), one of the most frequently used hypnotic agents. Quantitative sectional hair analyses of 1-mm segments were performed for each single-strand hair using a validated LC-MS/MS procedure. ZP was detected in all specimens plucked at 10 and 24 hours after a single dose, and the distribution ranged over the whole hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 33 publications
4
31
0
2
Order By: Relevance
“…Because the S 1 values for ME and EP were close to the S 2 values for DC and CP, the sweat/sebum route might be more dominant than the blood route for the uptake of ME and EP into hair. Shima et al recently reported, using 1‐mm segments which correspond to a growth length of 2.5 days, that the distributions of zolpidem and methoxyphenamine within a hair strand mapped to 2 regions with high concentrations . Both zolpidem and methoxyphenamine generated 2‐peak profiles, bulb‐origin and dermas‐origin peaks.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because the S 1 values for ME and EP were close to the S 2 values for DC and CP, the sweat/sebum route might be more dominant than the blood route for the uptake of ME and EP into hair. Shima et al recently reported, using 1‐mm segments which correspond to a growth length of 2.5 days, that the distributions of zolpidem and methoxyphenamine within a hair strand mapped to 2 regions with high concentrations . Both zolpidem and methoxyphenamine generated 2‐peak profiles, bulb‐origin and dermas‐origin peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Shima et al recently reported, using 1-mm segments which correspond to a growth length of 2.5 days, that the distributions of zolpidem and methoxyphenamine within a hair strand mapped to 2 regions with high concentrations. 18,19 Both zolpidem and methoxyphenamine generated 2-peak profiles, bulb-origin and dermas-origin peaks. The intensity of dermas-origin peak was comparable to the intensity of bulb-origin peak for methoxyphenamine, while the bulb-origin peak was more dominant than the dermas- The average ± standard deviation (SD) was calculated using values obtained from 20 strands of hair (ie, all strands of hair except for nos.…”
Section: Differences In Localizations Between Analytesmentioning
confidence: 99%
See 3 more Smart Citations